(untitled) (Research, Society and Development, 2021)
Objective: to identify nurses’ knowledge about Fetal Alcohol Syndrome (FAS) and the actions promoted by them in the prenatal care of pregnant women who are alcohol users in Basic Health Units (BHU). Method: A qualitative, descriptive and exploratory research was carried out in UBS, located in a city in the interior of Minas Gerais. Data were collected through interviews and, for interpretation, the content analysis technique was used. Results: eleven nurses participated in this study. From the information analyzed, three thematic categories emerged. Thematic Category 1: lack of knowledge about Fetal Alcohol Syndrome; Thematic Category 2: strategies used by nurses in the care of alcohol-using pregnant women; and, Thematic Category 3: difficulties in making reference and counter-reference in the health care network (RAS). Conclusion: It was concluded that nurses have little knowledge regarding the teratogenic effects of alcohol, and their actions are based on actively searching for pregnant alcohol users in an attempt to establish the therapeutic bond. Among the difficulties related to the theme, the one that most impacts the assistance process is the lack of an agreed flow that respects the obligations related to reference and counter-reference in the health care network. The search for professional improvement in Women’s Health and Mental Health, as well as the establishment of an adequate flow of care in the network, would ensure integral care to the pregnant woman and the newborn.